Tunisia : First and Second Reviews Under the Stand-By Arrangement, Request for Waiver of Applicability and Nonobservance of Performance Criteria. - International Monetary Fund. Middle East and Central Asia Dept. (Washington, D.C. : International Monetary Fund, 2014)
This paper discusses Tunisia's First and Second Reviews under the Stand-By Arrangement, Request for Waivers of Applicability and Nonobservance of Performance Criteria. Program performance has been mixed. Weak budget composition, lower budget commitments, and deferred cash payments to 2014 resulted in overshooting of the end-December fiscal target for the central government primary balance. The implementation of structural reforms has been progressing, but with some delays linked to building a consensus during the political crisis and to technical difficulties. Looking ahead, the program will continue to focus on ensuring short-term macroeconomic stabilization while laying the foundations for sustained reforms that will reduce economic vulnerabilities and generate higher and more inclusive growth. The IMF staff supports the authorities' request for completion of the combined first and second review.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet